Identification method for dental alloy type using a cosine similarity program: A preliminary investigation - Hori, Miki; Uematsu, Yasuaki; Kato, Akiko; Hori, Tadasuke; Sekine, Hironao; Ohno, Yuzo; Kawai, Tatsushi (Dental materials journal, 2023)
Although dental evidence is frequently used for the identification of unidentified persons, information about the many types of alloys used in prosthetics is not utilized. If the type of alloy can be identified from a small amount of material, the scope of the search could be narrowed. In this experiment, a method was investigated for identifying the alloy type using 3 kinds of cutting points (a white point and 2 types of silicone points). Wavelength-dispersive X-ray spectroscopy (WDS) was used for elemental analysis. The elements were translated into multidimensional vectors, and the cosine similarity was calculated to compare vectors of the WDS results and vectors of the official data of alloys. According to the results, cosine similarity showed a concordance of more than 0.8. The developed program is expected to be useful as a method for identifying alloy types using only a small amount of grinding dust.